Experimental study on the metal transfer control by using pulsed Ar addition in CO2 arc welding process: studies on pulsed gas MAG welding. Issue 7 (1st September 2020) - Fujiwara, Kohei; Tsuyama, Tadahisa; Ohara, Masahiro; Mizuguchi, Takashi; Mukai, Naoki; Inoue, Yoshihide
ABSTRACT: CO2 gas-shielded arc welding, which is widely used in the industrial world, has been recognized as an efficient and economical GMA welding process. However, its characteristic repelled transfer produces a large amount of spatter which results in costly cleanup and, thus, practical methods to overcome this weakness have been highly demanded. In the series of this study, 'Pulsed Gas MAG' welding was proposed as a new approach to reducing spatter, in which Ar gas pulses were periodically injected into CO2 shielding gas so that gas composition of arc atmosphere was largely modiﬁed in a very short period of time and a metal droplet formed at the electrode tip during CO2 atmosphere was released before repelled transfer had occurred. In this report, the inﬂuence of parameters of Ar gas injections, such as frequencies, average gas ﬂow rates and gas injection periods, on the metal transfer was investigated. It was found that synchronous metal transfer stimulated by pulsed Ar gas injections was achieved at any frequencies from 35 to 65 Hz under the conditions of gas injection periods longer than 4 ms and of Ar gas volumes larger than approximately 1mL/pulse. This is because Ar gas injections below these critical levels resulted in lack of time for arc shape changes and metal drop detachment. From these experimental results, a model to explain the metal transfer phenomena was developed. The amount of spatter was reduced to the levels as low as that of the conventional MAG welding with 80 %Ar +20 %CO2 shielding gas mix and penetration proﬁles were round shape like those obtained in CO2 arc welding.